Transport of nonequilibrium charge carriers in sensors based on chromium-compensated gallium arsenide under the influence of high-intensity synchrotron radiation - Trofimov, M. S. (Двадцать первая Всероссийская конференция студенческих научно-исследовательских инкубаторов, Томск, 13−17 мая 2024 г. : сборник трудов)
An important stage in the development and design of semiconductor detectors is carrying out scientific research to study the mechanisms of current flow in semiconductor sensors when exposed to ionizing radiation of various natures. In this work, we studied the transport of charge carriers in microstrip sensors based on chromium-compensated gallium arsenide when exposed to synchrotron radiation in the X-ray range. The computeraided semiconductor design system COMSOL was used as a research tool.